Measuring Urinary Sensation with Current Perception Threshold: A Comparison between Method of Limits and Method of Levels. (20th October 2011) - Davis, Carley; Lowenstein, Lior; Mueller, Elizabeth; Brubaker, Linda; Kenton, Kimberly
Abstract : Purpose . To determine the association between the two methods of obtaining current perception thresholds (CPTs) in the lower urinary tract (LUT). Materials and Methods . Twenty-one women undergoing pelvic surgery underwent CPT determinations of the urethra. CPTs were measured at 2, 000, 250, and 5 Hz (corresponding to A-β, A-δ, and C fibers, resp.) both pre- and postoperatively. Threshold values were obtained in all patients by using the method of limits and the method of levels. Results . CPT values obtained by using the method of levels and the methods of limits were highly correlated at all frequencies before and after surgery (ρ = 0.93 –0.99, P < 0.0001 ). The mean threshold values obtained by the method of levels were significantly lower at all frequencies compared with those obtained by the method of limits. Conclusions . Our findings suggest that the method of levels is more sensitive for the detection of CPTs compared to the method of limits.